Analysis of the Influence and Impact of social media on Gen-Z Literacy Activities - Regi Ginanjar (Insan Kreasi Media, 2025)
This article examines related to find out social media platforms influence both literacy development and the everyday lives of Generation Z in Indonesia. In this digital genertaion and this modern era, viral application such as TikTok, Instagram, and YouTube have become deeply embedded in the daily routines and learning habits of young people. While such media enhance access to knowledge and encourage creativity, with the frequent use of social media, there is increasing concern in society to erode traditional literacy skills. This study adopts a descriptive qualitative approach, combining literature analysis with online surveys involving 100 respondents aged 18–27. Researche’s statements about their findings on social media contributes positively to digital literacy and self-expression, it tends to reduce engagement in deep reading and coherent writing practices. Approximately 60% of participants favor short-form content, indicating a possible decline in attention span. Nevertheless, educational content on social media also inspires learning for some users. The researcher’s findings are that that social media functions dually—supporting informal education while also distracting from conventional literacy. The government must be combining digital literacy programs and encourage mindful content consumption among students.